2022
DOI: 10.1111/jeb.14016
|View full text |Cite
|
Sign up to set email alerts
|

Complex effects of environment and Wolbachia infections on the life history of Drosophila melanogaster hosts

Abstract: Wolbachia bacteria are common endosymbionts of many arthropods found in gonads and various somatic tissues. They manipulate host reproduction to enhance their transmission and confer complex effects on fitness‐related traits. Some of these effects can serve to increase the survival and transmission efficiency of Wolbachia in the host population. The Wolbachia–Drosophila melanogaster system represents a powerful model to study the evolutionary dynamics of host–microbe interactions and infections. Over the past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 111 publications
3
34
0
Order By: Relevance
“…In line with this hypothesis, it was shown that Wolbachia interferes with pheromone production in females during pupariation and affects female-to-male communication (Pontier et al, 2015). Additionally, two recent papers demonstrated the absence of Wolbachia effects on locomotion and fitness at juvenile stage of wild-caught D. nigrosparsa (Detcharoen et al, 2020) and D. melanogaster flies (Strunov et al, 2022). The absence of Wolbachia effects on host juvenile traits is challenged by a study, which reported stable abundance of Wolbachia transcripts at all stages of host development (Gutzwiller et al, 2015), although there was no data on translation of the transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this hypothesis, it was shown that Wolbachia interferes with pheromone production in females during pupariation and affects female-to-male communication (Pontier et al, 2015). Additionally, two recent papers demonstrated the absence of Wolbachia effects on locomotion and fitness at juvenile stage of wild-caught D. nigrosparsa (Detcharoen et al, 2020) and D. melanogaster flies (Strunov et al, 2022). The absence of Wolbachia effects on host juvenile traits is challenged by a study, which reported stable abundance of Wolbachia transcripts at all stages of host development (Gutzwiller et al, 2015), although there was no data on translation of the transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we show that members of two different castes in a social trematode harbour distinct microbiomes, and we further propose that the microbiomes of individuals might play a role in caste development. There is mounting evidence that an individual's microbiome can shape its phenotype (Diaz Heijtz et al, 2011 ; Feldhaar, 2011 ; Leclair et al, 2016 ; Strunov et al, 2022 ; Takacs‐Vesbach et al, 2016 ). On evolutionary timescales, microbiomes may even allow rapid adaptation (Alberdi et al, 2016 ) as well as influence animal speciation (Miller et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that an individual's microbiome, or the microbial community it harbours, can influence its development and eventual phenotype (Diaz Heijtz et al, 2011 ; Feldhaar, 2011 ). Among conspecific animals, distinct morphotypes or life history strategies are often associated with distinct endosymbiotic microbial communities (Leclair et al, 2016 ; Strunov et al, 2022 ; Takacs‐Vesbach et al, 2016 ). In social insects, members of different castes within the same colony often harbour different microbial symbionts (Kapheim et al, 2015 ; Koto et al, 2020 ; Poulsen et al, 2014 ), though whether the acquisition of a particular microbial community precedes or follows the developmental adoption of a particular caste remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As wMel Wolbachia increases female lifespan in D. melanogaster 61 and in wMel transinfected Ae. albopictus 62 , we asked if Wolbachia infection alters Ae.…”
Section: Wolbachia Increases the Lifespan Of Virgin Aedes Aegypti Fem...mentioning
confidence: 98%